Genetic fine mapping of systemic lupus erythematosus MHC associations in Europeans and African Americans. (31st July 2018) - Hanscombe, Ken B; Morris, David L; Noble, Janelle A; Dilthey, Alexander T; Tombleson, Philip; Kaufman, Kenneth M; Comeau, Mary; Langefeld, Carl D; Alarcon-Riquelme, Marta E; Gaffney, Patrick M; Jacob, Chaim O; Sivils, Kathy L; et al.
Abstract: Genetic variation within the major histocompatibility complex (MHC) contributes substantial risk for systemic lupus erythematosus, but high gene density, extreme polymorphism and extensive linkage disequilibrium (LD) have made fine mapping challenging. To address the problem, we compared two association techniques in two ancestrally diverse populations, African Americans (AAs) and Europeans (EURs). We observed a greater number of Human Leucocyte Antigen (HLA) alleles in AA consistent with the elevated level of recombination in this population. In EUR we observed 50 different A—C—B—DRB1—DQA—DQB multilocus haplotype sequences per hundred individuals; in the AA sample, these multilocus haplotypes were twice as common compared to Europeans. We also observed a strong narrow class II signal in AA as opposed to the long-range LD observed in EUR that includes class I alleles. We performed a Bayesian model choice of the classical HLA alleles and a frequentist analysis that combined both single nucleotide polymorphisms (SNPs) and classical HLA alleles. Both analyses converged on a similar subset of risk HLA alleles: in EUR HLA– B * 08:01  +  B * 18:01  + ( DRB1 * 15:01 frequentist only) +  DQA * 01:02  +  DQB * 02:01  +  DRB3 * 02 and in AA HLA –C * 17:01  +  B * 08:01  +  DRB1 * 15:03  + ( DQA * 01:02 frequentist only) +  DQA * 02:01  +  DQA * 05:01 + DQA * 05:05  +  DQB * 03:19  +  DQB * 02:02 . We observed two additional independent SNP associations in both populations: EUR rs146903072 and rs501480; AA rs389883 and rs114118665. The DR2 serotype was best explained by DRB1 * 15:03  +  DQA * 01:02 in AA and by DRB1 * 15:01  +  DQA * 01:02 in EUR. The DR3 serotype was best explained by DQA * 05:01 in AA and by DQB * 02:01 in EUR. Despite some differences in underlying HLA allele risk models in EUR and AA, SNP signals across the extended MHC showed remarkable similarity and significant concordance in direction of effect for risk-associated variants.